Prevalence and Factors Predictive of Full Stomach in Elective and Emergency Surgical Patients: A Prospective Cohort Study. Issue 4 (August 2017) - Bouvet, L.; Desgranges, F. P.; Aubergy, C.; Boselli, E.; Dupont, G.; Allaouchiche, B.; Chassard, D.
Abstract : (Abstracted from Br J Anaesth, 118(3):372–379, 2017) The purpose of this prospective cohort study was to determine whether the stomachs of patients undergoing surgery, either elective or emergency, were empty or full. In addition, the authors sought to assess the causes and risks of a full stomach, which can lead to pulmonary aspiration of gastric contents as well as surgical mortality from general anesthesia.